Genetic Models of Leukemia in Zebrafish - Baeten, Jeremy T.; Jong, Jill L. O. de (Frontiers in Cell and Developmental Biology, 2018)
The zebrafish animal model is gaining increasing popularity as a tool for studying human disease. Over the past 15 years, many models of leukemia and other hematological malignancies have been developed in the zebrafish. These confer some significant advantages over similar models in other animals and systems, representing a powerful resource for investigation of the molecular basis of human leukemia. This review discusses the various zebrafish models of lymphoid and myeloid leukemia available, the major discoveries that have been made possible by them, and opportunities for future exploration.